1996
DOI: 10.1088/0268-1242/11/12/026
|View full text |Cite
|
Sign up to set email alerts
|

High-performance GaInP/AlGaInP strained quantum well lasers grown by solid source molecular beam epitaxy

Abstract: High-performance visible (λ ≈ 680 nm) Ga x In 1−x P/(Al y Ga 1−y ) 0.51 In 0.49 P compressively strained single quantum well laser diodes have been grown by solid source molecular beam epitaxy. The waveguide region was designed to have a low Al content in order to enhance the optical field confinement and to improve the material quality. The threshold current density for an infinity long cavity length was estimated to be 150 A cm −2 . The highest external quantum efficiency of 37% per facet was obtained for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…5,6 We have also made similar preliminary experiments with encouraging results on SSMBE-grown phosphide-based lasers. 7,8 In the present letter, we have investigated in more detail the influence of RTA on Ga x In 1Ϫx P/(Al y Ga 1Ϫy ) 0.51 In 0.49 P strained-layer QW lasers grown by SSMBE. We show that there exist optimal RTA conditions which lead to a remarkable reduction in J th without deteriorating other lasing features.…”
Section: Effects Of Rapid Thermal Annealing On Gainp/algainp Lasers Gmentioning
confidence: 99%
“…5,6 We have also made similar preliminary experiments with encouraging results on SSMBE-grown phosphide-based lasers. 7,8 In the present letter, we have investigated in more detail the influence of RTA on Ga x In 1Ϫx P/(Al y Ga 1Ϫy ) 0.51 In 0.49 P strained-layer QW lasers grown by SSMBE. We show that there exist optimal RTA conditions which lead to a remarkable reduction in J th without deteriorating other lasing features.…”
Section: Effects Of Rapid Thermal Annealing On Gainp/algainp Lasers Gmentioning
confidence: 99%
“…However, there has been limited success in the practical incorporation of AlGaInP MQB structures. Many groups have reported experimental evidence for improved device performance; [7][8][9] however, most recognize a disparity between enhancements found experimentally and those predicted theoretically. [10][11][12] In a previous publication, 13 we suggested that discrepancies between theoretical and experimental findings may be attributed to two oversimplifications in the simulations employed, namely, ͑i͒ the omission of an intervalley transport mechanism and ͑ii͒ neglecting to optimize the MQB at the working bias of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows a review of high-performance In x Ga 1-x P QW and InP MQD laser on GaAs with low-threshold pulsed and CW operation at RT [1][2][3][4][5][6][7][8][9][10][11][12]. Typical J th of 300 -550 A/cm 2 is observed for In x Ga 1-x P QW laser, with the lowest CW J th of 295 A/cm 2 [13].…”
mentioning
confidence: 99%